There is Still Vision/Hope – Choices of Optical Low Vision Aids (A-Z) - Prasanna Venkatesh Ramesh; Sathyan Parthasarathi; Shruthy Vaishali Ramesh; Aji Kunnath Devadas (Delhi Journal of Ophthalmology)
Low vision aids (LVA) are designed to provide improved visual acuity to a visually impaired patient who cannot be treated by regular refractive corrections or other treatments. The main purpose of LVA is not only visual rehabilitation but also social adaptation. A comprehensive understanding of the various available LVAs, their advantages and disadvantages is crucial for selecting the most suitable device for each patient. In this article, we talk about the various types of optical devices, its advantages and disadvantages and methods of prescription.